Modal Sosial Nelayan Remaja dalam Mengelola Sumber Daya Pesisir dan Arah Pengembangan Pendidikan Berkelanjutan - Berlian Birly Aeywaldy; Amirah Tsania Khansa; Anis Anis; Tania Januarti; Shakira Mahendra Putri; Putra Pratama Saputra (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
This study aims to examine the role of social capital among adolescent fishermen in managing natural resources as a survival strategy in the Pongok Islands District, South Bangka Regency. This study uses descriptive qualitative methods through interviews, participant observation, and documentation. This study found that the Pongok Islands District has great potential in the coastal sector, both from marine products and marine tourism. The lives of adolescent fishermen from the Malay and Bugis ethnic groups demonstrate strong social capital in the community, which is reflected in social ties that strengthen internal solidarity and cross-ethnic togetherness in fishing activities; social bridges that bridge fishermen with external parties in marketing catches and economic networks; and social links that connect the community with government institutions to gain access to assistance, training, and production facilities.